Estado da arte sobre bibliotecas escolares na Pós-graduação em Ciência da Informação no Brasil (2011-2020) - PINHEIRO, Iranildo Junior de Souza (Universidade Federal do Pará, 2024)
Despite the school library (BE) playing an important social, educational, informative, and cultural role, until the end of the 20th century, the theme did not receive due scientific recognition in Brazil. From the beginning of the 21st century, the discussion of the theme was endorsed, mainly, by the legislative debate that resulted in Law 12.244/2010 on the universalization of the school library in the country and caused an impact on technical and scientific communication on the subject, generating numerous studies on the production of this theme, which served as a reference for this work, compiled through narrative review (ABREU; GONÇALVES, 1998; CAMPELLO, 2003; CAMPELLO et al., 2007; CAMPELLO et al., 2013; LEMOS, 2015; SILVA, 2015 ; SILVA; VENTORIM, 2016; PASQUIM, 2016; GASQUE; CASARIN, 2016; OLIVEIRA; CAMPELLO, 2016; SILVA; OLIVEIRA, 2017; RITA; BLATTMANN, 2018; OLIVEIRA, 2019; OLIVEIRA, 2019; ROCHA; SANTO, 2019). This research seeks to analyze the Brazilian scientific production on BE in postgraduate studies in Information Science (IC). The study's overarching goal is to examine works defended between 2011 and 2020 with the central axis of investigation being BE in Graduate Programs in CI (PPGCIs). With the specific objectives of: discussing the context of research on BE in Librarianship and CI and reviews of scientific production on the subject in the area; describing the academic work on BE of PPGCIs in the last decade; and identifying, through content analysis (BARDIN, 2010), the thematic categories of the selected works. Therefore, a literature review was carried out with a systematic search in the Catalog of Theses and Dissertations of CAPES to present the report of the characteristics of the collected works, followed by the identification of 14 research themes on BE in the selected studies, compared with the thematic categories from the literature review (CAMPELLO et al., 2013; SILVA, 2015 and LEMOS, 2015). The results point to a low representativeness of BE in PPGCIs research in the last decade (2.94%) and reveal new research themes in postgraduate studies on BEs: information mediation, accessibility, management, information organization, and studies of historical aspects of the school library, in addition to those already known in previous studies. In general, the most discussed categories among the selected studies (Competence in Information, Reading, and the educational function of the BE) reinforce the primary function of the BE of contributing to the formation of students through the processes of reading development and search skills, as well as access and use of information for citizen information literacy.